A single apparatus for the production of ultracold fermionic lithium and cold bosonic caesium gases - Paris Mandoki, Asaf (2015)
Ultracold mixture experiments hold the promise of providing new insights into many-body quantum systems as well as ultracold chemistry and few-body phenomena. The work presented in this thesis dealt with the construction of a new apparatus for the production and study of ultracold gases of fermionic lithium-6 and bosonic caesium-133. These isotopes offer a wide tunability in their interaction strength, both in inter-species and intra-species collisions, through magnetic Feshbach resonances. Additionally, the widely different resonance frequencies of lithium and caesium enables independent control of each of the species.